Sexual dysfunction and quality of life across age groups in multiple sclerosis patients: a prospective cross-sectional analysis - Reza Dehghaniathar; Ali Faegh; Fahimeh Hajiakhoundi; Behnam Shakiba; Zeynab Najjar (BMC Neurology)
Abstract Introduction As the most frequent chronic neurological disorder in young adults, Multiple sclerosis (MS) significantly affects neurological function, particularly the autonomic nervous system. While the physical symptoms are visible, MS also causes hidden effects like sexual dysfunction. Research indicates that sexual disorders are more prevalent in MS patients compared to other neurological conditions and are approximately five times more common than in the general population. This study utilized the Sexual Intimacy and Desires in MS Patients Questionnaire (MSISQ-19) and the Quality of Life in Patients with Multiple Sclerosis Questionnaire to investigate the impact of sexual disorders on the quality of life in MS patients. Methods This cross-sectional study was conducted on MS patients attending the MS clinic in 2022 and 2023. Eighty patients were randomly selected, and data were collected using the MSISQ-19 and MSQOL-54 questionnaires. The results were analyzed to establish the impact of sexual disorders on quality of life. Results 59 women and 21 men with MS were included. The Physical Health Scale (PHC) had a mean score of 51.6 (SD = 20.2), and the Mental Health Scale (MHC) had a mean score of 57.8 (SD = 20.5). Age appeared to influence physical health scores, with the youngest group (20–30 years) scoring highest and the oldest group (51–65 years) scoring lowest. Discussion and conclusion The present study found that primary, secondary, and tertiary sexual disorders are common in MS patients across all age groups and genders. These findings highlight the need for increased attention, research, and treatment interventions for sexual dysfunction in MS patients.